The Application of Game-Based Learning “Hunt for Directions” to encourage student’s Interest in Learning Descriptive Texts - Devina Elvaretta Arrazaq; Fitriah Fitriah; Feriyal Feriyal (Universitas Cokroaminoto Palopo, 2025)
The low level of students’ interest in learning descriptive texts highlights the urgency of adopting innovative learning media to support language learning engagement. This study aims to measure the effectiveness of using the educational game “Hunt for Directions” to encourage learners’ interest in learning descriptive texts. This study attempts to address this issue through the application of innovative methods. A descriptive quantitative approach was employed, focusing on a single variable: students’ interest in learning. The subjects consisted of 32 seventh-grade students at MTs Negeri 4 Surabaya. Primary data were collected through questionnaires distributed to students after they received an intervention using the “Hunt for Directions” game during the learning process. The results show a significant increase in students’ average scores of learning interest. This increase was evident not only overall but also in specific key dimensions, such as enthusiasm, intrinsic motivation, and learners’ excitement when studying linguistic features and descriptive text structures. These findings indicate that educational games can serve as an effective medium for addressing the issue of low learning interest in language teaching. The results further show that the implementation of this game effectively enhanced students’ interest in learning, with the majority of students (approximately 96.875%) demonstrating a high level of attention and interest in descriptive texts after the intervention, particularly in terms of intrinsic motivation and understanding of text structure. In conclusion, the “Hunt for Directions” game proves to be an effective and promising strategy for increasing students’ interest in learning descriptive texts.